The role and regulation of Asterless in the centrosome cycle - Novak, ZA (2014)
Centrosomes are the main microtubule organizing centres in animal cells and are formed by a pair of centrioles together with surrounding pericentriolar material (PCM). Cycling cells duplicate their centrosomes strictly once per cell cycle. This process is driven by the semi-conservative duplication of the centrioles that are found at the centrosome core. During the exit from mitosis the two centrioles within the single inherited centrosome separate, and upon the start of S-phase each of these inherited mother centrioles assembles an adjacent daughter at its side. This process results in two complete centrosomes that can form the poles of the mitotic spindle, and thus segregate evenly to the next cell generation. The formation of a daughter centriole suppresses the initiation of new duplication events from the same templating mother centriole until this daughter separates - disengages - at the end of the cell cycle. This regulation - that acts to repress centriole amplification - is summarized in the 'licensing model of centriole duplication' (Tsou and Stearns, 2006). This model states that centriole disengagement provides the license for the re-duplication of mother centrioles. Importantly, experiments show that while abolishing centriole engagement is sufficient to allow mother centrioles to re-duplicate within the same cycle, it is insufficient to allow daughter centrioles the assembly of a granddaughter before they mature into mothers towards the end of their first cell cycle. The molecular nature of this daughter-to-mother transition remains mysterious. In this thesis I show that in Drosophila embryos the essential centriole duplication protein Asl is not incorporated into daughter centrioles as they assemble during S-phase, but is only incorporated once mother and daughter separate at the end of mitosis. The initial incorporation of Asterless (Asl) is irreversible, and is dependent on centriolar DSas-4. Crucially, Asl incorporation is essential for daughter centrioles to mature into mothers that can support centriole duplication. I propose that Asl acts as a permanent primary license that allows new centrioles to duplicate for the first time. Once acquired, this primary license is not lost but rather further regulation is taken over by the reduplication licensing mechanism, disengagement. This work extends the previously proposed licensing model to also explain how new centrioles are licensed for their first duplication event.